Comparison of contact stress distribution for foam seat and seat of auxetic spring skeleton - Janus-Michalska, Małgorzata; Jasińska, Dorota; Smardzewski, Jerzy (Zielona Góra: Uniwersytet Zielonogórski)
The objective of this paper is to present and compare the results of numerical solutions of contact problem for two types of seats subjected to typical sitting loadings. The first seat is made of a typical hyperelastic foam, the other is designed with an auxetic polyamid spring skeleton. Computer simulations of the seat structure under a typical static loading exerted by a human body are performed by means of ABAQUS FEA.
Keywords: auxetic structures; seat; utility load; contact problem